Prevalence of Psychological Distress, as Measured by the Kessler 6 (K6), and Related Factors in Japanese Employees. - Fushimi, Masahito; Saito, Seiji; Shimizu, Tetsuo; Kudo, Yasutsugu; Seki, Masayuki; Murata, Katsuyuki (Community Mental Health Journal, 2012)
The aim of this study was to examine the prevalence of and related factors for psychological distress among employees. The employees in Akita prefecture, Japan, were invited to complete the Kessler 6 (K6). A value of 13 or higher on the K6 scale indicated high psychological distress. Furthermore, we identified the relationships among the prevalence of high psychological distress, socio-demographic status, and employment-related variables. The data of 1,709 employees indicated that 10.8% of the employees had high psychological distress; the proportion of psychological distress found in the present study was high compared to that found in previous studies. The identified socio-demographic and occupation-related factors included young age groups associated with a high risk and clerical or administrative tasks associated with a low risk of psychological distress. The data of this study can be used as K6 benchmark values, which enhance the significance of future corporate health risk appraisal surveys.